1983
DOI: 10.1210/endo-113-5-1858
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Stimulation of Luteinizing Hormone Secretion in the Female Monkey: Influence of Endocrine and Experimental Conditions*

Abstract: It is known that opiate administration results in the inhibition of LH release. In this paper, we examine the role of endogenous opiates in the regulation of gonadotropin secretion during the menstrual cycle of the monkey. The objectives of these experiments were to determine the experimental and endocrine conditions that are conducive to increased gonadotropin secretion in response to endogenous opiate antagonism. In Exp 1, naloxone was administered during the luteal phase to three groups of monkeys under thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
1

Year Published

1987
1987
1994
1994

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 15 publications
3
29
0
1
Order By: Relevance
“…This was expected since FSH does not appear to be acutely regulated by GnRH in the sheep (Clarke & Cummins, 1985b). Other work in the rat (Sirinanthsinghji & Martini, 1985;Piva et al, 1985), monkey (Van Vugt et al, 1983) and human (Foresta et ai, 1983;Snowden et al, 1984) has also indicated that FSH is unresponsive to naloxone treatment, perhaps for similar reasons. However, Ropert et al (1981) have shown that FSH does respond to an infusion of naloxone in women.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This was expected since FSH does not appear to be acutely regulated by GnRH in the sheep (Clarke & Cummins, 1985b). Other work in the rat (Sirinanthsinghji & Martini, 1985;Piva et al, 1985), monkey (Van Vugt et al, 1983) and human (Foresta et ai, 1983;Snowden et al, 1984) has also indicated that FSH is unresponsive to naloxone treatment, perhaps for similar reasons. However, Ropert et al (1981) have shown that FSH does respond to an infusion of naloxone in women.…”
Section: Discussionmentioning
confidence: 80%
“…Brooks et al (1986b) also noted that the ability of naloxone to increase LH secretion in Suffolk-cross ewes varied, and further showed that there was no dose-response relationship between 25 and 100 mg/h. Similarly, Van Vugt et al (1983) demonstrated that only 60% of lutealphase monkeys had an LH response to naloxone. Finally, chronic treatment of rams with naloxone led to a loss of responsiveness after 3 days (Ebling & Lincoln, 1985).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Mild stress (chair restraint) in nonhuman primates arrests the GnRH pulse generator (8), an effect mediated by the corticotropin-releasing factor (CRF) (9,10). CRF infusion in humans causes an inhibition of pulsatile LH release (11).…”
Section: Adult Reproductive Functionmentioning
confidence: 99%
“…When estrogen levels are high, injection of the p-endorphin antagonist naloxone increases serum LH levels and can even advance the LH surge in women by an average of 2 d (Rossmanith et al, 1988). In contrast, naloxone has very little effect on LH release when E, levels are low (Van Vugt et al, 1983). Ovariectomy in rats results in an increase in basal LH levels that are reduced by injection of estradiol (Legan et al, 1973).…”
mentioning
confidence: 99%